Clinical features, epidemiology, and short-term outcomes of proliferative lupus nephritis in Eastern India - Sircar, D; Sircar, G; Waikhom, R; Raychowdhury, A; Pandey, R (Indian journal of nephrology, 2013)
Race and ethnicity are important predictors of prognosis in lupus nephritis. This study was conducted to determine the clinical features, epidemiological profile, and short-term outcomes in patients of lupus nephritis from a single center in Eastern India. A total of 86 patients of class III/IV lupus nephritis were studied. Seventy-eight of them received cyclophosphamide for induction and eight of them received mycophenolate. The patients were evaluated for response, estimated glomerular filtration rate (eGFR), and proteinuria at 6 months. About 44% patients had a partial or complete response at 6 months and 64% at 1 year. The factors correlating with response at 6 months were older age at diagnosis, hypertension, activity, and chronicity indices and duration of symptoms prior to therapy. Chronicity index and hypertension were the predictors of response by logistic regression at 6 months. Compared to the Caucasian and African American patients, patients with proliferative lupus in Eastern India presented with a lower eGFR, lower proteinuria, and higher chronicity scores. Older age at diagnosis, hypertension, activity, chronicity indices, and duration of symptoms correlated with response. Short-term outcomes were similar to those described in Caucasian patients.